Is preoperative ultrasound tumor size a prognostic factor in endometrial carcinoma patients? - Ambrosio, Marco; Raffone, Antonio; Alletto, Andrea; Cini, Chiara; Filipponi, Francesco; Neola, Daniele; Fabbri, Matilde; Arena, Alessandro; Raimondo, Diego; Salucci, Paolo; Guerrini, Manuela; Travaglino, Antonio; et al. (Frontiers in Oncology, 2022)
Objective We aimed to assess the prognostic value of preoperative ultrasound tumor size in EC through a single center, observational, retrospective, cohort study. Methods Medical records and electronic clinical databases were searched for all consecutive patients with EC, preoperative ultrasound scans available to ad hoc estimate tumor size, and a follow-up of at least 2-year, at our Institution from January 2010 to June 2018. Patients were divided into two groups based on different dimensional cut-offs for the maximum tumor diameter: 2, 3 and 4 cm. Differences in overall survival (OS), disease specific survival (DSS) and progression-free survival (PFS) were assessed among the groups by using the Kaplan–Meier estimator and the log-rank test. Results 108 patients were included in the study. OS, DSS and PFS did not significantly differ between the groups based on the different tumor diameter cut-offs. No significant differences were found among the groups sub-stratified by age, BMI, FIGO stage, FIGO grade, lymphovascular space invasion status, myometrial invasion, lymph nodal involvement, histotype, and adjuvant treatment. Conclusions Preoperative ultrasound tumor size does not appear as a prognostic factor in EC women.